1-Methyl-7-(4-nitrophenyl)-3-phenylpyrazolo[3,4-b]pyrrolo[3,4-d]pyridine-6,8(3H,7H)-dione - Sabino, Jose R. (International Union of Crystallography, 2008)
In the title compound, C(21)H(13)N(5)O(4), the dihedral angles formed between the planes of the phenyl and nitrophenyl rings and that of the heterotricyclic plane are 41.29 (7) and 61.35 (6)°, respectively. In the crystal, weak C—H⋯O interactions help to establish the packing.